Membandingkan Kekuatan Pengelasan Single Dan Double Kawat Inti Elektroda (Filler Rod) Menggunakan Las Smaw - Hendarto, Dede Hendri; Susandi, Dony (Universitas Majalengka, 2024)
Advances in welding technology are very helpful in making, repairing or repairing chassis jobs that have a high level of difficulty and requirements. Especially in the chassis, many welding elements are involved because welded joints have an important role to support the body, engine, and vehicle load. In practical work at CV. Pringgandani Welding Analysis Comparing the Strength of Welding Results of Single Electrode Core Wire and Double Electrode Core Wire (Filler Rod) Using SMAW welding which is carried out for chassis welding which is claimed by mechanics in welding with a depth and width of more than 5 mm, it is better to use double electrode core wire which can speed up and strengthen the weld. Then a test is carried out to prove the results of the Single Wire Electrode Core and Double Electrode Core Wire (Filler Rod) welds which are stronger and faster in the process. By testing the weld results on an iron plate with dimensions of 250 mm x 50 mm x 10 mm, the welding process uses the SMAW (Shielded Metal Arc Welding) welding method. Using an E6013 type electrode with a diameter of 2 mm with a current of 90 A, polarity DCEP (Direct Current Electrode Positive) The welding position used is the 1G position or horizontal position with the welding process using a single v-groove bevel butt joint and an angle of 60o with a weld width of 10 mm and a weld depth of 8 mm. The plate samples used were two samples. In sample 1 using a single wire core electrode, and sample 2 using a double wire core electrode. All samples were made of tensile test specimens with the ASME-IX standard, a tensile test was carried out to determine and prove the respective strengths of the welding results of Single Wire Core Electrode and Double Wire Core Electrode (Filler Rod).